Perancangan Desain Umkm Di Kota Padang “Daus Kunci” Dalam Implementasi Komunikasi Grafis - Dicky Syafhotra; Tiara Sesilia Ingrid; Ilham Gusral; Zulfahmi (CV. ITTC INDONESIA, 2025)
This research discusses the role of graphic communication in supporting visual design for developing the Daus Kunci MSME brand identity. As a micro business actor in the field of key duplication services, Daus Kunci needs an effective visual strategy to increase its attractiveness and competitiveness in a competitive market. Through a graphic communication approach, visual elements such as logos, typography and colors are analyzed and redesigned to convey the value and unique characteristics of the product in a consistent and attractive manner. This research uses a qualitative descriptive method with case studies, field observations, and direct interviews with MSME owners. The results show that implementing appropriate graphic communication can improve brand image, strengthen visual identity, and build positive consumer perceptions of products. This study confirms the important role of visual communication design as a strategic tool in the sustainable development of MSMEs.